Are Prophylactic Intravenous Antibiotics Required in Routine Shoulder Arthroscopic Surgery? A Systematic Review of the Literature - Baraza, Njalalle; Leith, Jordan (Joints, 2018)
Purpose The purpose of this study was to find out from the literature the difference in infection rates between patients who did and patients who did not receive prophylactic antibiotics in arthroscopic shoulder surgery.Methods We conducted a comprehensive search of the literature using Medline Ovid for prospective studies that looked at infection as the primary outcome following shoulder arthroscopy. The articles were then assessed for study design, outcome, and relevance to the specific question as part of the critical appraisal.Results Eight partially relevant articles were obtained from the search, but there were no prospective studies comparing infection in patients who had prophylactic antibiotics versus those who did not in shoulder arthroscopy.Conclusion No compelling evidence exists on the role of prophylactic antibiotics in preventing infections in shoulder arthroscopy.Level of Evidence Level IV, systematic review of level IV studies.
Keywords: shoulder arthroscopy; prophylactic antibiotics; arthroscopic surgery; infection